2018
DOI: 10.1242/jcs.218305
|View full text |Cite
|
Sign up to set email alerts
|

Ivy1 is a negative regulator of Gtr-dependent TORC1 activation

Abstract: The highly conserved TORC1 complex controls cell growth in response to nutrients, especially amino acids. The EGO complex activates TORC1 in response to glutamine and leucine. Here, we demonstrate that the I-BAR domain-containing protein Ivy1 colocalizes with Gtr1 and Gtr2, a heterodimer of small GTPases that are part of the EGO complex. Ivy1 is a negative regulator of Gtr-induced TORC1 activation, and is contained within puncta associated with the vacuolar membrane in cells grown in nutrient-rich medium or af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
(86 reference statements)
2
14
0
Order By: Relevance
“…Cells lacking Vps1 showed a growth defect at 37°C, but Vps1-GFP expressing cells grew as well as the WT cells, suggesting that this Vps1-GFP is functional (Figure S4A). Consistent with a previous report (Varlakhanova et al, 2018), Vps1-GFP colocalized with endosomal Nhx1-mCherry, but not with Golgi localized Sec7-mCherry (Figure S4B and S4C). We also confirmed that Vps1-GFP colocalized with Mvp1-mRFP (Figure S4D).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Cells lacking Vps1 showed a growth defect at 37°C, but Vps1-GFP expressing cells grew as well as the WT cells, suggesting that this Vps1-GFP is functional (Figure S4A). Consistent with a previous report (Varlakhanova et al, 2018), Vps1-GFP colocalized with endosomal Nhx1-mCherry, but not with Golgi localized Sec7-mCherry (Figure S4B and S4C). We also confirmed that Vps1-GFP colocalized with Mvp1-mRFP (Figure S4D).…”
Section: Resultssupporting
confidence: 93%
“…In this mutant, membrane scission of clathrin-coated vesicles is blocked. This lysine residue is widely conserved in dynamin-related GTPases, including Vps1 (Figure 4F and S4E; Varlakhanova et al, 2018; Tornabene et al, 2020). To test if the GTP hydrolysis activity of Vps1 is required for Vps55 recycling, we examined Vps55 localization in vps1 K42A mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Cells lacking Vps1 showed a growth defect at 37°C, but Vps1-GFP-expressing cells grew as well as the WT cells, suggesting that this Vps1-GFP is functional ( Figure 4—figure supplement 1A ). Consistent with a previous report ( Varlakhanova et al, 2018 ), Vps1-GFP colocalized with endosomal Nhx1-mCherry, but not with Golgi-localized Sec7-mCherry ( Figure 4—figure supplement 1B, C , C). We also confirmed that Vps1-GFP colocalized with Mvp1-mRFP ( Figure 4—figure supplement 1D ).…”
Section: Resultssupporting
confidence: 92%
“…48 Ivy1, an effector of the vacuolar Rab GTPase Ypt7 49 and inhibitor of the Fab1 complex 50 colocalizes with Fab1 and the EGO complex to dots proximal to the vacuole. 49,51 We now present evidence that signaling endosomes have a key function in endosome and vacuole membrane homeostasis. Ivy1, Fab1, the EGO complex, and TORC1 all localize to signaling endosomes in addition to their vacuolar localization.…”
Section: Introductionmentioning
confidence: 89%
“…Both Ivy1, as a Fab1 inhibitor, and TORC1 localize to the vacuole and distinct dots. [49][50][51] As Ivy1 localization was unaffected by ESCRT-III deletions, 49 we previously discarded the possibility that Ivy1 resides also on endosomes. However, it was recently shown that a second population of endosomes exists, which contains an endosomal pool of TORC1 and the EGO complex.…”
Section: Torc1 and Fab1 Localize To Signaling Endosomes And Interact mentioning
confidence: 99%